2018
DOI: 10.1111/1365-2435.13125
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mitochondrial metabolic requirements in fasting animals carry an oxidative cost

Abstract: Summary Many animals experience periods of food shortage in their natural environment. It has been hypothesised that the metabolic responses of animals to naturally‐occurring periods of food deprivation may have long‐term negative impacts on their subsequent life‐history.In particular, reductions in energy requirements in response to fasting may help preserve limited resources but potentially come at a cost of increased oxidative stress. However, little is known about this trade‐off since studies of energy met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 61 publications
(111 reference statements)
3
61
1
1
Order By: Relevance
“…There are also reversible changes in relative organ size (and hence metabolic rate) when animals are faced with major energetic challenges such as long-distance migrations [70] or infrequent but large meals [71,72]. Components of mitochondrial structure and function can also shift in response to changes in ATP requirement [1,73] and/or resource availability [74][75][76], with the typical response being an increase in the efficiency of ATP production (measured as ATP produced per unit consumption of oxygen) when conditions are more challenging [74,75]. However, mitochondrial responses can differ between organs (and even between muscle types) of the same individual [74,77], and increases in mitochondrial efficiency can come at a cost of increased rates of ROS production, which may explain why ATP production efficiency is not always maximized [76].…”
Section: Physiological/cellular Mechanisms Underlying (Changes In) Mementioning
confidence: 99%
“…There are also reversible changes in relative organ size (and hence metabolic rate) when animals are faced with major energetic challenges such as long-distance migrations [70] or infrequent but large meals [71,72]. Components of mitochondrial structure and function can also shift in response to changes in ATP requirement [1,73] and/or resource availability [74][75][76], with the typical response being an increase in the efficiency of ATP production (measured as ATP produced per unit consumption of oxygen) when conditions are more challenging [74,75]. However, mitochondrial responses can differ between organs (and even between muscle types) of the same individual [74,77], and increases in mitochondrial efficiency can come at a cost of increased rates of ROS production, which may explain why ATP production efficiency is not always maximized [76].…”
Section: Physiological/cellular Mechanisms Underlying (Changes In) Mementioning
confidence: 99%
“…Studies have shown that moderate energy restriction enhances resistance to oxidative stress and increases the mean and maximum healthy lifespan in many organisms (Sohal et al, 1994;López-Torres et al, 2002;Bevilacqua et al, 2004;Bevilacqua et al, 2005;Fontana et al, 2010;Walsh et al, 2014). In contrast, an extreme reduction in available energy such as that during fasting may induce pro-oxidant effects including, in some incidents, enhanced mitochondrial ROS production or free electron leak (ROS/O), and their subsequent negative impact on cellular integrity and life span (Sorensen et al, 2006;Fontana et al, 2010;Brown and Staples, 2011;Salin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Longer-lived snake species have lower ROS production (Robert, Brunet-Rossinni, & Bronikowski, 2007), and long-versus short-lived ecotypes of Thamnophis elegans exhibit divergence in mitochondrial genes of the electron transport chain (Schwartz, Arendsee, & Bronikowski, 2015), a principle site of ROS production (Turrens, 2003). Indeed, the few studies to investigate aphagous animals suggest fasting induces a pro-oxidant state [elephant seals (Sharick et al, 2015); fish (Morales et al, 2004, Morales et al 2011, Pascual et al, 2003, Salin et al, 2018; King penguins (Schull et al, 2016); rats (Sorensen et al, 2006)]. Given the relatively long turnover rate of blood cells in general (e.g.…”
Section: Discussionmentioning
confidence: 99%